2007
DOI: 10.1007/s00737-007-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression and treatment with inner city pregnant and parenting teens

Abstract: Interpersonal contexts may be pivotal in contributing, maintaining and/or alleviating depression among poor urban pregnant and newly parenting adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…[296][297][298] Of these, one study also reported perspectives and attitudes of service providers on selective preventive interventions. [296][297][298] l Three studies presented data from those who had received an indicated preventive intervention. 253,256,299,300 One study, with a separate citation, 301 additionally reported on the perspectives of and attitudes of service providers on indicated preventive interventions.…”
Section: Qualitative Studies Level Of Preventive Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…[296][297][298] Of these, one study also reported perspectives and attitudes of service providers on selective preventive interventions. [296][297][298] l Three studies presented data from those who had received an indicated preventive intervention. 253,256,299,300 One study, with a separate citation, 301 additionally reported on the perspectives of and attitudes of service providers on indicated preventive interventions.…”
Section: Qualitative Studies Level Of Preventive Interventionmentioning
confidence: 99%
“…Twelve studies reported qualitative data on the perspectives and attitudes of those who had received universal preventive interventions for PND [277][278][279][280][281][282][283][284][285][286][287][288][289] (of these, two also reported perspectives and attitudes of service providers on universal preventive interventions 287,288 and two studies reported only on the perspectives and attitudes of service providers to preventive interventions). 290,291 l Four studies presented data from those who had received a selective preventive intervention [292][293][294][295][296][297][298] (with one study additionally presenting data relating to an indicated population). [296][297][298] Of these, one study also reported perspectives and attitudes of service providers on selective preventive interventions.…”
Section: Qualitative Studies Level Of Preventive Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se debe tener en cuenta que los sín-tomas anímicos muchas veces se confunden con las características de este período adaptativo (36). En el caso de las jóvenes, los síntomas depresivos suelen acompañarse tanto de tristeza como de irritabilidad (37).…”
Section: Discussionunclassified
“…We also explored the ministers' opinion about conducting an evidence-based treatment for MDD, interpersonal psychotherapy (IPT) delivered in a group, [41][42][43] at the church. This intervention was selected because it has been shown to be effective among similar populations, 44,45 including two studies conducted in groups with community members in rural Uganda.…”
Section: Introductionmentioning
confidence: 99%